Visualization of oil-lubrication ball bearings at high rotational speeds - Tohyama, Mamoru; Ohmiya, Yasuhiro; Hirose, Michiru; Matsuyama, Hiroki; Toda, Takuya; Hasegawa, Kenichi; Onizuka, Takaaki; Sato, Hideaki; Yokoi, Masahiro; Sato, Norikazu (Frontiers in Mechanical Engineering, 2024)
Deep-groove ball bearings for the eAxles of electric vehicles must adapt to higher rotational speed conditions because the speed of eAxle motors have been increasing as the size and weight of the motors decrease. Therefore, understanding the oil-lubricated conditions inside ball bearings at high rotational speeds is essential for optimizing their design for eAxles. To clarify the oil-lubricated conditions inside ball bearings at these high speeds, a new test apparatus was developed. This apparatus is capable of simultaneously measuring the friction torque of deep-groove ball bearings, the oil-film thickness on the rolling balls, and observing the oil distributions inside the bearings at rotational speeds up to 20,000 min -1 . The oil-film thickness was measured using three-wavelength optical interferometry, and the oil distribution was observed using fluorescence. It was found that the oil-film thickness became constant at rotational speed conditions exceeding approximately 7,700 min -1 . Oil starvations were observed on the raceway around the rolling ball, and these regions increased with increasing rotational speeds. Additionally, in the deep-groove ball bearing with a crown-shaped cage, the oil was mainly supplied to the rolling balls from the inner ring side through the space between the cage claws that held the ball. Moreover, the amount of mixed air tended to increase as the rotational speed increased to approximately 7,700 min -1 . Those oil starvations and increasing air in oils were considered to be factors that prevent the increase in oil-film thickness. The findings of the reported study will contribute to the development of multibody dynamic technology for high-speed ball bearings necessary in electric vehicles.